Espectro de controle, comportamento em misturas e intervalo de segurança para a semeadura de soja e algodão para os herbicidas dicamba E 2,4-D - Osipe, Jethro Barros (2015)
The development of cultivars resistant to herbicides has been consolidated with an important tool in weed control. After the generation of resistant crops to glyphosate, other news should appear on the market. The use of mimics of auxin herbicides such as 2,4-D and dicamba, post-emergence of the crop will be an innovation in the next years. However, updated information relating to the herbicide dicamba is scarce in Brazil, because the herbicide has left the market a few decades ago. This work aims at the potential use of dicamba herbicide in weed management, comparing it to the herbicide 2,4-D. With respect to post-emergence control, the herbicide 2,4-D was superior to dicamba for control of Brazilian pusley (Richardia brasiliensis), spiderwort (Commelina benghalensis) and morning glory (Ipomoea nil). For plants from hairy fleabane (Conyza spp.), buttonweed (Spermacoce latifolia) and arrowleaf sida (Sida rhombifolia), the dicamba herbicide exercised greater control than 2,4-D. With the addition of glyphosate to the auxin mimic the differences between these herbicides have been less pronounced. For smaller plants (4-6 leaf), mixtures of glyphosate + 2,4-D or dicamba + glyphosate have provided excellent levels of control for all species. The mixture of ACCase-inhibiting herbicides and auxin mimics has not been considered antagonistic to the control horseweed. As for the sourgrass, antagonism was observed between these herbicides in some situations, which was more evident for larger plants. The herbicide 2,4-D had more cases of antagonism of the dicamba in mixtures with ACCase inhibiting herbicides. The mixtures with the graminicide quizalofop showed more antagonistic than the mixtures containing clethodim. The applications of auxin mimics herbicides in pre-sowing soybeans and cotton operation may affect the initial growth of the crops. The soybean crop was more sensitive to pre-sowing herbicide dicamba than to 2,4-D applications. In such cases, the safety intervals for the application of these herbicides can exceed 28 days for dicamba, and reach up to 8 days for 2,4-D. The cotton crop was less sensitive to the application of dicamba than soybean. Security interval obtained for applications in pre-sowing of cotton with dicamba was up to 11 days, and for 2,4-D, were up to 9 days.